THE INFLUENCE OF GOVERNMENT EXPENDITURE IN THE EDUCATION, HEALTH, AND INFRASTRUCTURE SECTORS ON THE HUMAN DEVELOPMENT INDEX IN ACEH PROVINCE 2018-2024 - BR Tarigan, Rosana Aginta; Saharuddin, Saharuddin (Journal of Malikussaleh Public Economics, 2025)
This study aims to determine the effect of government spending in the education, health, and infrastructure sectors on the human development index in Aceh province. This study uses a combination of cross-section data with time series in 23 regencies/cities in Aceh Province during 2018-2024. The data analysis method used is Panel Data Regression with the help of eviews 10. The results of this study prove that Government Spending in the Education Sector and Health Sector have a positive and significant effect on the human development index, while Government Spending in the Infrastructure Sector has a negative and significant effect on the human development index. The magnitude of the influence of Government Spending in the Education, Health and Infrastructure Sectors on the Human Development Index is 28.12 and the remaining 71.88 is influenced by other variables outside this model. It is recommended that the Regency/City governments in Aceh Province can realize government spending in the Education, Health and Infrastructure Sectors properly, so that the economy in Aceh is stable and people's welfare increases.